Islamic Education at the Nizhamiyah Madrasah during the Abbasid Era: Models of Financing, Curriculum Design, and Pedagogical Priorities - Anggraini, Reni Dwi; Kawakib, Ahmad Nurul (Yayasan Abdurrauf Cendekia Nusantara, 2025)
This article discusses the relationship between financing patterns and educational curriculum in the Nizhamiyah Madrasah during the heyday of the Abbasid Daulah in Baghdad. The problem studied is how the funding system through government waqf influenced the structure and orientation of the curriculum in the madrasa. The purpose of this study is to reveal the impact of the financing system on the focus of the applied educational curriculum. This research uses descriptive-analytical method with primary and secondary data collection through literature study of Islamic education history. The results show that the funding pattern sourced from waqf influenced the establishment of a curriculum dominated by religious sciences, especially fiqh, as part of the effort to strengthen Sunni theology. Teaching focused on the Shafi'i school of thought and was staffed by prominent scholars of the time. In addition, efficient financial management by the government contributed to the availability of adequate educational facilities. Thus, it can be concluded that the financing system played a significant role in shaping the curriculum of the Nizhamiyah Madrasah, which was directed at producing a cadre of leaders who excelled in the fields of religion and government. Abstrak: Artikel ini membahas hubungan antara pola pembiayaan dan kurikulum pendidikan di Madrasah Nizhamiyah pada masa kejayaan Daulah Abbasiyah di Baghdad. Permasalahan yang dikaji adalah bagaimana sistem pendanaan melalui wakaf pemerintah memengaruhi struktur dan orientasi kurikulum di madrasah tersebut. Tujuan penelitian ini adalah untuk mengungkap dampak sistem pembiayaan terhadap fokus kurikulum pendidikan yang diterapkan. Penelitian ini menggunakan metode deskriptif-analitis dengan pengumpulan data primer dan sekunder melalui studi literatur sejarah pendidikan Islam. Hasil kajian menunjukkan bahwa pola pendanaan yang bersumber dari wakaf memengaruhi penetapan kurikulum yang didominasi oleh ilmu-ilmu keagamaan, khususnyafiqih, sebagaibagiandariupayapenguatanteologi Sunni. Pengajarandifokuskan pada mazhab Syafi’i dan dikelola oleh ulama-ulama terkemuka pada masanya. Selain itu, manajemen keuangan yang efisien oleh pemerintah turut menunjang tersedianya fasilitas pendidikan yang memadai. Dengan demikian, dapat disimpulkan bahwa sistem pembiayaan berperan signifikan dalam membentuk kurikulum Madrasah Nizhamiyah, yang diarahkan untuk mencetak kader pemimpin yang unggul dalam bidang keagamaan dan pemerintahan. Kata kunci: Pembiayaan, Kurikulum, Madrasah Nizhamiyah